Identification of a new fish trypanosome from the large yellow croaker (Larimichthys crocea) and description of its impact on host pathology, blood biochemical parameters and immune responses - Yang Xiaoao; Qi Pengzhi; Tao Zhen; Zhang Qingwei; Wang Yanjie; Zhu Denghui; Yan Xiaojun; Fu Peipei; Guo Baoying (Parasite)
The aim of this study was to clarify the taxonomic identification of a hemoflagellate and assess the effect of trypanosome infection on Larimichthys crocea. Giemsa staining showed the presence of three morphotypes of trypomastigotes. The trypanosomes had the following morphological characteristics: a slender body with a long flagellum at the front; body size 12.30–30.90 × 1.13–2.33 μm; elongated oval nucleus situated in the median region; kinetoplast small, oval, located at the posterior end. The parasite had significant morphological differences from Trypanosoma epinepheli Su, Feng, Jiang, Guo, Liu & Xu, 2014 and Trypanosoma carassii (Mitrofanov) Doflein, 1901. The 18S rDNA sequences of the trypanosome from L. crocea had the highest homology (98.4%) with T. carassii. Phylogenetic analysis indicated that the parasite clustered with freshwater fish trypanosomes. Based on the differences in morphological characteristics and molecular data, it is considered a new species, Trypanosoma larimichthysi n. sp. Trypanosome infection had no effect on the growth of L. crocea, but significantly increased the concentration of blood urea nitrogen (BUN), and induced pathological changes in the gills, liver, spleen and kidney. The pro-inflammatory immune genes, including TNF-α, IFN-γ, IL-1β, CXCL8 and iNOS, were significantly upregulated in the L. crocea infected with trypanosomes. These results suggest that the trypanosome has negative impacts on host health.